2022
DOI: 10.1248/cpb.c21-00834
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpy–Entropy Compensation in the Structure-Dependent Effect of Nonsteroidal Anti-inflammatory Drugs on the Aqueous Solubility of Diltiazem

Abstract: Certain combinations of acidic and basic drugs can cause significant changes in physicochemical properties through the formation of ionic liquids, eutectic mixtures, or deep eutectic solvents. In particular, combining indomethacin and lidocaine is known to result in apparent increases in both the partition coefficients (hydrophobicity) and aqueous solubilities (hydrophilicity). The physicochemical interactions between drugs change the water solubility of the drugs and affect the bio-availability of active phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…There was a large difference between the polymorphs in the ATR-FTIR spectra, especially in the 1800-1600 cm −1 range, corresponding to the differential C]O stretching vibration depending on the hydrogen bonds in the crystal. 27,53,54 Both the thermograms and spectra of the samples were in good agreement with previously reported data on the aand g-forms, indicating that two pure polymorphic forms of INM were obtained. The measured and published XRPD diffractograms of the aand g-forms are conrmed as described in Materials and Methods in Fig.…”
Section: Identication Of Inm Polymorphssupporting
confidence: 90%
See 4 more Smart Citations
“…There was a large difference between the polymorphs in the ATR-FTIR spectra, especially in the 1800-1600 cm −1 range, corresponding to the differential C]O stretching vibration depending on the hydrogen bonds in the crystal. 27,53,54 Both the thermograms and spectra of the samples were in good agreement with previously reported data on the aand g-forms, indicating that two pure polymorphic forms of INM were obtained. The measured and published XRPD diffractograms of the aand g-forms are conrmed as described in Materials and Methods in Fig.…”
Section: Identication Of Inm Polymorphssupporting
confidence: 90%
“…Chatani et al 23 reported that the solubility of a drug is influenced by buffer components, such as phosphate, Britton–Robinson universal prescription, imidazolium salt, and a variety of Good's buffers. Kinoshita et al 27 claimed the entropy-enthalpy compensation of variable combinations of solubilizers to prevent the formation of a soluble complex. Hereafter, it is expected to yield a solution under the conditions of a thermodynamically homogeneous solute dissolved from heterogeneous polymorphic crystals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations